Benzodithiophene Hole‐Transporting Materials for Efficient Tin‐Based Perovskite Solar Cells. (4th September 2019) - Vegiraju, Sureshraju; Ke, Weijun; Priyanka, Pragya; Ni, Jen‐Shyang; Wu, Yi‐Ching; Spanopoulos, Ioannis; Yau, Shueh Lin; Marks, Tobin J.; Chen, Ming‐Chou; Kanatzidis, Mercouri G.
Abstract: Developing efficient interfacial hole transporting materials (HTMs) is crucial for achieving high‐performance Pb‐free Sn‐based halide perovskite solar cells (PSCs). Here, a new series of benzodithiophene (BDT)‐based organic small molecules containing tetra‐ and di‐triphenyl amine donors prepared via a straightforward and scalable synthetic route is reported. The thermal, optical, and electrochemical properties of two BDT‐based molecules are shown to be structurally and energetically suitable to serve as HTMs for Sn‐based PSCs. It is reported here that ethylenediammonium/formamidinium tin iodide solar cells using BDT‐based HTMs deliver a champion power conversion efficiency up to 7.59%, outperforming analogous reference solar cells using traditional and expensive HTMs. Thus, these BDT‐based molecules are promising candidates as HTMs for the fabrication of high‐performance Sn‐based PSCs. Abstract : Low‐cost and efficient organic small molecules are desired as hole transporting materials for high‐performance perovskite solar cells. Two new molecules containing a benzodithiophene core and triphenylamine side chains are synthesized from cheap starting materials by a simple and low‐cost method. Lead‐free, tin‐based perovskite solar cells employing these new benzodithiophene‐based hole transporting materials achieve good efficiencies.